2008
DOI: 10.1039/b810171j
|View full text |Cite
|
Sign up to set email alerts
|

Acid–base properties and DNA-binding of water soluble N-confused porphyrins with cationic side-arms

Abstract: Water soluble N-confused porphyrins, 5,10,15,20-tetrakis(alpha-pyridinio-p-tolyl)-2-aza-21-carbaporphyrin (pPyNCP) and its N-methyl derivative, 2-N-methyl-5,10,15,20-tetrakis(alpha-pyridinio-p-tolyl)-2-aza-21-carbaporphyrin (NMe-pPyNCP), have been synthesized by introducing cationic side-arms at the meso-positions of N-confused porphyrin. Their acid-base properties (pK(1-4)) and DNA-binding ability in aqueous solutions were elucidated in comparison with the corresponding porphyrin derivative. Photophysical beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…To investigate interactions between porphyrins and group I ribozymes, we employed meso -tetraarylporphyrins ( Figure 1 ) as a core platform structure because they have been used frequently in designing porphyrin-based functional molecules [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In this study, we primarily used pPyP and pPyNCP ( Figure 1 ) [ 23 , 28 ]. pPyP and pPyNCP have been shown to interact with various forms of DNA molecules, including single- and double-stranded DNAs [ 23 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate interactions between porphyrins and group I ribozymes, we employed meso -tetraarylporphyrins ( Figure 1 ) as a core platform structure because they have been used frequently in designing porphyrin-based functional molecules [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In this study, we primarily used pPyP and pPyNCP ( Figure 1 ) [ 23 , 28 ]. pPyP and pPyNCP have been shown to interact with various forms of DNA molecules, including single- and double-stranded DNAs [ 23 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chemical syntheses of pPyP and pPyNCP were reported previously [ 23 ]. TMPyP was purchased from Sigma-Aldrich (St.…”
Section: Methodsmentioning
confidence: 99%
“…[13,14] Watersoluble derivatives of 5,10,15,20-tetrakis(4'-sulfophenyl) porphyrin Investigations of inverted porphyrins properties, including aqueous media, have been carried out since their discovery due to the unique structure of these compounds. [15][16][17][18][19][20][21][22][23][24][25] Previously it was shown that diprotonated inverted platform possesses the properties of anionic receptor, [8,26] the zwitterions H 4 IP 2+ (PhSO 3 -) 4 and H 3 MeIP 2+ (PhSO 3 -) 4 are able to form supramolecular J-aggregates, stable in pHneutral aqueous solutions. [21,27] In this work we presented the results of theoretical and experimental studies of…”
Section: Introductionmentioning
confidence: 99%
“…Biological applications of N-confused porphyrins are an intriguing and still less explored area. It has been observed that cationic N-confused porphyrin derivatives can bind to DNA [26] or stabilize G-quardruplex DNA [27]. N-confused porphyrins have also been proved efficient photosensitizer against breast adenocarcinoma cells [25].…”
Section: Introductionmentioning
confidence: 99%